CRIME PREVENTION IN UZBEKISTAN (Лучшие интеллектуальные исследования, 2025)
Crime prevention is pivotal for maintaining stability and social order in Uzbekistan. Ongoing political and socio-economic reforms have prompted comprehensive measures to combat crime in all its forms—from youth delinquency to cyber threats—through legal, institutional, and community-based interventions reddit.com+8grnjournal.us+8uzswlu.uz+8ijournal.uz+15theasiatoday.org+15en.wikipedia.org+15.